Analysis of Urban Marginal Expansion Based on Remote Sensing Means and Its Impacts on Landscape Pattern Changes - Ban, Jingyun (Transactions on Environment, Energy and Earth Sciences, 2024)
The rapid expansion and development of the city have introduced a large number of surrounding rural populations into the city, resulting in the continuous outward expansion of the city area. The expansion of the town leads to changes in the morphology and number of patches in the urban fringe area, and a larger degree of expansion leads to loosen urban morphology, landscape fragmentation, and a reduction in the efficiency of land use, resulting in a series of problems such as loss of arable land, waste of resources, and damage to the ecological environment. Landscape pattern is an expression of land use, and a series of problems brought about by urban expansion will directly cause the evolution of landscape patterns. This paper introduces the research methods and main techniques of urban edge expansion based on remote sensing techniques and analyses the impact of urban edge expansion on the evolution of landscape patterns. Results show that studying urban edge expansion based on remote sensing technology includes buffer analysis using remote sensing data, establishing landscape indicators, and then discussing their impacts on the evolution of landscape patterns. The buffer zone analysis can identify the buffer zones of different circles to determine the scope of urban expansion in various periods, while the landscape pattern index analysis can evaluate the evolution of landscape patterns after the calculation and statistics of data. Finally, the impact of urban expansion on landscape pattern changes is mainly reflected in the fragmentation, heterogeneity, and complexity of the landscape.